Older adults and mental health during the social distancing period of Covid-19 (Research, Society and Development, 2022)
Introduction: Population around the world has been suffering from social and psychological implications due to the coronavirus pandemic. Older adults are considered to be the most vulnerable group to the effects of social distancing, mainly because of fear and the uncertainties of the pandemic. Objective: To identify the post-isolation psychological impacts on the elderly population. Methods: Descriptive, cross-sectional and observational study with 50 participants over 60 years old from Londrina- PR. Questionnaires from the Geriatric Depression Scale 15 (GDS-15), Geriatric Anxiety Inventory (GAI) were applied, and clinical demographic data were obtained. Statistical analyzes were evaluated by linear regression models and bivariate correlations using Kendall’s tau-b coefficient. Results: In this study, 36% of the participants had a score higher than expected in the GDS and GAI questionnaires, which were predicted by self-reports of moments of sadness and anxiety (b=0.426; t=2.94; p=0.005) and by the decrease of social contact (b=0.346; t=2.31; p=0.027), respectively, in the absence of previous psychological disorders. Conclusion: There was a low incidence of depressive and anxiety symptoms in this age group.